Strategi Bauran Pemasaran di Agrowisata Buana Ametha Sari - Pasaribu, Nami Fitricia (Bina Nusantara University, 2013)
Object of this research is Agrowisata Buana Amertha Sari, Bali. Limitation on this study is marketing mix, especially on product and promotion. Coffee is the main comodity in Agrowisata Buana Amertha Sari, while promotion is conducted through words of mouth method and in cooperation with local guides. Agrowisata Buana Amertha Sari uses website to promote its products. Within this research, it is expected the use of social media Facebook and Twitter could make contribution in boosting the recognition to global customers. This research is qualitative using interview and observation at one time in May 2013.